(untitled) (Vietnam Journal of Community Medicine, 2024)
Anesthesia for giant mediastinal tumors is always a challenge for anesthesiologists. Regardless of diagnosis, all large mediastinal masses can compress or invade vital structures, severely affecting breathing and circulation. Thoroughly detailed preoperative preparation is very important for surgical outcomes, including surgical imaging diagnosis, focusing on vascular anatomy and tumor invasion characteristics. A multidisciplinary discussion between radiologists, anesthesiologists, and surgeons is very important. With adequate preoperative team planning, a safe anesthetic and surgical strategy can be implemented. In particular, high-risk cases need to be performed in hospital that can establish extracorporeal circulation in the shortest time to ensure safety for anesthesia and surgery. We report 2 cases, diagnosed with a giant mediastinal tumor that was compressing the respiratory and circulatory system, and surgery was performed to remove the tumor under anesthesia. The patients were anesthetized and operated, including one case of successful extubation and one case of postoperative death. Conclusion: In cases where giant mediastinal tumors compress the respiratory and circulatory system, the patient’s anesthesia strategy is very important to ensure patient safety